The sanitary plumbing of a modern house - Allen, Marian (My University, 1904)
Introduction: Good housekeeping is always difficult. With every modern convenience at her command the housewife will still find many calls upon her time and strength. If she be wise she will take advantage of everything that will lighten the labor for her. There is no doubt but that a good sewage system saves an immense amount of time and labor. It carries away all the waste products from the house and relieves the home keeper of this drudgery. Such a system is economical in dollars and cents. When the overburdened worker in the house breaks down and doctor’s bills are due the “head of the house” realizes that he might have been saved this expense by easing the labors of his helpmate and there preventing the break down, by the inauguration of a good system of sewage disposal. It saves a great amount of wear and tear on clothing, especially shoes thus reducing the family shoe bill. It is economical again in making doctor’s bills unnecessary by preventing sickness. It is a sanitary arrangement in every respect. It carries away filth, that would cause disease, with speed, it prevents soil contamination and thereby drinking water. Foul gases are kept from entering the house as would come if the waste material was left to lie and decay about the yard. There is grave danger to health from sewer gas and this subject is discussed fully in the succeeding pages.
Citation: Allen, Marian. The sanitary plumbing of a modern house. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Sewage systems; Sewage disposal; Economic advantages of sewage systems; Sanitary benefits; Theses